Faunal analysis of the historic component at Healy Lake Village site, Interior Alaska - Hilmer, Hilary A. (2019)
Thesis (M.A.) University of Alaska Fairbanks, 2019 The historic period in Interior Alaska was a dynamic time that led to many cultural changes for Native Alaskan communities across the state. Starting in the early 1700s, Russian and Euroamerican explorers began interacting with Native Alaskan groups living on the coast and by the end of the 18th century - early 19th century, Interior Alaskan groups were being directly affected. Due to western influences, Native groups, such as the Upper Tanana Athabascans, began to rely on a cash economy, causing them to settle to year-round villages, trade with the Euroamericans for non-local goods (i.e., flour, guns, buttons, glass, and nails), and work on construction projects in order to provide for their families. All of these changes appeared to cause a division between the traditional way of life and the new Euroamerican way of living. Healy Lake Village site (XBD-00020) is a multi-component site with occupations spanning the terminal Pleistocene into the Holocene. It is located approximately 100 miles southeast of present day Fairbanks on the shores of Healy Lake in the Upper Tanana Athabascan territory. The village was a summer fishing camp until ~A.D. 1910; it became a year-round village soon after the construction of a trading post at Healy Lake. The well-preserved faunal remains excavated from the Upper Cultural level (dating to A.D. 1880 - 1946) at Healy Lake Village site provide a significant opportunity to address fundamental questions relating to subarctic hunter-gatherer subsistence economies. This research employs concepts from human behavioral ecology and world-systems theory to address questions relating zooarchaeological patterns in the data in terms of taphonomy, human procurement, and processing decisions, as well as historic period land use strategies and trade practices. In this thesis, I explore the possibility that the residents at Healy Lake Village site were affected by Euroamerican influences, specifically in regards to their subsistence ...